Memórias de Leitura de Pessoas Idosas - Vetter, Silvana Maria de Jesus (2006)
This work consists of an inquiry on the memories of reading of aged people. It has for objective to rescue the memories of reading of these people, through its verbal stories, method that in allows them to bring to emerge the lived process already, using the chance to destroy the ready images, instituted socially. With this study, we look for to answer to the following questions: How was given the practice of the reading in the Maranhão, enters been born in the decades of 1920 the 1950? How was the relation of the people with the book? It had easiness of access to the library? The reading materials were gotten through loan between familiar and friends, or purchases? To rescue important points of the cultural history of the reading, we count on the abomination of the studies of Bosi (1994); Certeau (1972); Chartier (1998;1996); Halbwachs (1990); Le Goff (1994); Manguel (1997), among others that they had served for the theoretical construction of this research. Thus, with this study, in the circumstances of the verbal stories, we evidence that the historical process of the reading results of the register of the memory, divulged in the social relations, through a constant exercise of the reading. In this perspective, it is valid to say that if many people do not read, it is because it did not have in its memories the register of the necessity of the reading for its own life.